Spinal Cord Stimulation 50 Years Later: Clinical Outcomes of Spinal Cord Stimulation Based on Randomized Clinical Trials—A Systematic Review. Issue 4 (May 2018) - Mekhail, Nagy; Visnjevac, Ogi; Azer, Gerges; Mehanny, Diana Sue; Agrawal, Priya; Foorsov, Victor
Abstract : Abstract: To assess the efficacy of spinal cord stimulation (SCS) for each indication, one must critically assess each specific clinical outcome to identify outcomes that benefit from SCS therapy. To date, a comprehensive review of clinically relevant outcome-specific evidence regarding SCS has not been published. We aimed to assess all randomized controlled trials from the world literature for the purpose of evaluating the clinical outcome-specific efficacy of SCS for the following outcomes: perceived pain relief or change pain score, quality of life, functional status, psychological impact, analgesic medication utilization, patient satisfaction, and health care cost and utilization. Interventions were SCS, without limitation to the type of controls or the type of SCS in the active arms. For each study analyzed, a quality assessment was performed using a validated scale that assesses reporting, external validity, bias, confounding, and power. Each outcome was assessed specific to its indication, and the primary measure of each abovementioned outcome was a summary of the level of evidence. Twenty-one randomized controlled trials were analyzed (7 for trunk and limb pain, inclusive of failed back surgery syndrome; 8 for refractory angina pectoris; 1 for cardiac X syndrome; 3 for critical limb ischemia; 2 for complex regional pain syndrome; and 2 for painful diabetic neuropathy). Evidence assessments for each outcome for each indication were depicted in tabular format. Outcome-specific evidence scores were established for each of the abovementioned indications, providing both physicians and patients with a summary of evidence to assist in choosing the optimal evidence-based intervention. The evidence presented herein has broad applicability as it encompasses a breadth of patient populations, variations of SCS therapy, and comparable controls that, together, reflect comprehensive clinical decision making.